The Effect of Ramadan Fasting on Cognition in Young Adults - Koul, Ahlam Saleem; Tariq, Esha (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Fasting has been practiced for centuries, often for religious or spiritual reasons, and has gained popularity in recent years for its potential health benefits. During Ramadan, Muslims fast from sunrise to sunset for several days, which may impact various bodily functions, including cognition. Previous research has explored the effects of fasting on cognition, with some studies suggesting no significant cognitive impact. However, these studies often overlooked mild cognitive dysfunctions that may not be immediately apparent but could influence daily functioning, and such a change demands facilitation and acknowledgement by society. Objectives: This study aimed to investigate the impact of Ramadan fasting on cognitive function in young adults, specifically evaluating changes in cognition before and during fasting. Materials and Methods: A quasi-experimental design was utilized with 24 students from Rawalpindi Medical University. Cognitive performance was assessed using the Montreal Cognitive Assessment (MoCA) both before and during Ramadan fasting. Data were analyzed using paired-sample t-tests and Wilcoxon-Signed Rank tests. Results: Significant reductions in cognitive scores were observed during fasting (24.3 ± 2.2) compared to non-fasting (28.4 ± 0.9), with a p-value of 0.009. Short-term memory scores decreased significantly during fasting (11.4 ± 2.9) versus non-fasting (14.9 ± 0.4, p = 0.009). Word production also declined significantly (fasting: 10.3 ± 3.7; non-fasting: 13.4 ± 2.8, p = 0.002). Effect sizes were large for overall cognition and short-term memory and medium for word production. These results suggest a potential mild cognitive decline during Ramadan fasting. Conclusion: Ramadan fasting is associated with significant reductions in cognitive performance among young adults, particularly affecting short-term memory and word production. These findings highlight the potential cognitive challenges faced during fasting, which could impact academic and professional performance. Key Words: Cognition, fasting, memory, mental status and dementia tests, mental recall